Using Collaborative Strategic Reading (CSR) to Improve Reading Comprehension of Vocational School Students (An experimental study at SMK Negeri 1 Dampal Selatan, Toli-Toli, Central Sulawesi) - Erniwati, Erniwati; Darmawan, Darmawan; Kamaruddin, Abdul; Amalia, Rezki (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
This study aims to determine if Collaborative Strategic Reading (CSR) affects the reading comprehension of grade ten students of SMK Negeri 1 Dampal Selatan. It used a quasi-experimental design with two groups called experimental and control groups, and involved 52 grade ten students as the samples. The paper-and-pencil method was used for data collection, with tests as the instrument. The pretest and posttest tests were administered to both groups. Data obtained from the tests were analyzed statistically to determine the sampled students’ reading comprehension before and after the treatment. The result showed that the reading comprehension of the experimental group improved significantly compared to the control one. Using a degree of freedom (df) of 50 and a significance level (ρ) of 0.05, it was found that the t-counted was 8.79, which was higher than the t-table of 1.677. Because the t-counted value was greater than the t-table value, the research hypothesis was accepted. Thus, using Collaborative Strategic Reading is effective for improving the reading comprehension of the sampled students of grade ten at SMK Negeri 1 Dampal Selatan.